2021
DOI: 10.1136/bmjgh-2020-004022
|View full text |Cite
|
Sign up to set email alerts
|

Learning from changes concurrent with implementing a complex and dynamic intervention to improve urban maternal and perinatal health in Dar es Salaam, Tanzania, 2011-2019

Abstract: IntroductionRapid urbanisation in Dar es Salaam, the main commercial hub in Tanzania, has resulted in congested health facilities, poor quality care, and unacceptably high facility-based maternal and perinatal mortality. Using a participatory approach, the Dar es Salaam regional government in partnership with a non-governmental organisation, Comprehensive Community Based Rehabilitation in Tanzania, implemented a complex, dynamic intervention to improve the quality of care and survival during pregnancy and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…It is also possible that the higher NMR in urban areas in Tanzania can be partly explained by the under-reporting of neonatal death in rural areas; these deaths might have been misclassified as stillbirths or not reported at all. 42 However, the Tanzania DHS 2015-2016 results showed that also the perinatal mortality rate (stillbirths and early neonatal deaths per 1000 pregnancies of seven or more months' duration) was higher in urban (47) compared to rural areas (37). If this bias plays a role in the findings in our paper, it is therefore more likely to operate through under-reporting of perinatal deaths in rural areas rather than through differential misclassification of neonatal deaths as stillbirths.…”
Section: Bmj Global Healthmentioning
confidence: 50%
See 1 more Smart Citation
“…It is also possible that the higher NMR in urban areas in Tanzania can be partly explained by the under-reporting of neonatal death in rural areas; these deaths might have been misclassified as stillbirths or not reported at all. 42 However, the Tanzania DHS 2015-2016 results showed that also the perinatal mortality rate (stillbirths and early neonatal deaths per 1000 pregnancies of seven or more months' duration) was higher in urban (47) compared to rural areas (37). If this bias plays a role in the findings in our paper, it is therefore more likely to operate through under-reporting of perinatal deaths in rural areas rather than through differential misclassification of neonatal deaths as stillbirths.…”
Section: Bmj Global Healthmentioning
confidence: 50%
“…Given the pressure exerted by population increase in urban areas on existing resources, particularly public health facilities providing care to the poor, it is possible that crowding, staff shortages, and lack of routine provision of essential care elements converge in such urban health facilities and contribute to increased risk of neonatal mortality. [37][38][39] Additionally, the risk of acquiring nosocomial infections within health facilities is particularly relevant to premature and lowbirth newborns who are highly vulnerable to acquiring and dying from such infections.…”
Section: Discussionmentioning
confidence: 99%
“…Second, one may question the claim that the LCG sets off ‘revolutionary steps towards individualized labour care’, as it is not context‐stratified to the available resources 1 . Maternity units in low‐ and low‐ to middle‐income countries are increasingly congested and the human resources crisis is tremendous 8,9 . It is impossible to follow the LCG surveillance regime if caring for more than two women simultaneously 4 .…”
Section: Disclosure Of Interestsmentioning
confidence: 99%
“…The hospitals are typical examples of overburdened urban maternity units in a lower-middle-income country, where the quality of care is impacted by lack of physical infrastructure, human resources and supplies. In 2019, the selected hospitals jointly cared for 40% of all hospital-based births in Dar es Salaam [ 19 ]. Each birth attendant typically takes care of multiple women simultaneously.…”
Section: Methods and Analysismentioning
confidence: 99%